Replication of "How Much Does Immigration Boost Innovation?" - Taylor Wright (Institute for Replication (I4R), 2022)
A common approach to identifying the causal impact of immigration on outcomes involves using a "shift-share" or Bartik instrument exploiting country-specific immigration in ows (shifts) and location specific prior shares for the same countries. New econometric findings suggest this instrumental variables approach uses identifying variation not from the shifts, as previously believed, but rather from the shares and suggest a battery of checks to explore the sensitivity of estimates. In this note, I first replicate Hunt and Gauthier-Loiselle (2010) which estimates the effects of immigration on innovation via patenting, and second deploy these new checks from the econometric literature on shift-share instruments. I find that the results of Hunt and Gauthier-Loiselle (2010) (skilled immigration increases innovation and has positive spillovers on the innovation of others) replicate and hold up well to these new tests.
Keywords: 330